The Impact of Dry Needling on Patients with Neck Pain in a Tertiary Hospital - Ho, SE.; Loong, S.; Fatin Nur Laily R.; Wan Nur Aizzati M.; Muhamad Firdaus IZ.; Christopher, Ho CK.; Katijah Bee MA.; Henry, LJ.; Ismail MS. (Department of Surgery, UKM Medical Centre, 2015)
Neck pain presents as a symptom of dull pain or discomfort mainly along the trapezius muscle. Dry needling is an invasive procedure which uses acupuncture needle directed at myofascial trigger points. The aim of the study was to evaluate the effectiveness of dry needling in managing patients with neck pain. A pre-test-post-test interventional study design was used. Patient education package was provided to 32 respondents who fulfilled the inclusion criteria. A 13-item Pain Catastrophizing Scale (PCS) questionnaire was used to assess Rumination, Magnification and Helplessness. Subjective pain intensity was measured by Visual Analogue Scale (VAS). These questionnaires were given before and after the dry needling intervention. The findings reported that respondents scored high in pre-test total PCS score (27.41±13.652). Post-test result revealed a significant improvement in total PCS score (23.06±13.938) (p = 0.000). Post-test VAS score (4.78±1.237) was also significantly better than pre-test (6.47±1.414) (p = 0.000). There was no significant difference in pre-test PCS in terms of marital status (p > 0.05) whereas there was significant difference between marital status and rumination in post-test (Z = -2.303, p = 0.021). There was significant difference between pre-test magnification in terms of respondents’ occupation (p = 0.008) and race (p = 0.035) but no significant difference in post-test. Respondents’ age group showed no significant differences between pre-test and post-test PCS and VAS (p > 0.05). In conclusion, patients who received dry needling showed improvement in pain intensity and catastrophizing towards neck pain.